Impact of Xylomethazoline on Eustachian Tube Function in Healthy Participants. Issue 5 (June 2015) - Meyer, Moritz F.; Mikolajczak, Stefanie; Korthäuer, Christine; Jumah, Masen D.; Hahn, Moritz; Grosheva, Maria; Lüers, Jan-Christoffer; Hüttenbrink, Karl-Bernd; Beutner, Dirk
<x xml:space="preserve">Abstract</x> Introduction The use of decongestants is common in otitis media eustachian tube (ET) dysfunction. However, the underlying mechanism and the type of action on the complex middle ear pressure equalization system are poorly understood. Here, by use of the pressure chamber, we investigated the impact of intranasal decongestive therapy (xylomethazoline) on ET function. Materials and Methods Thirty healthy participants (60 ears) were exposed to a predetermined profile of phases of compression and decompression in a hypobaric and hyperbaric pressure chamber. ET opening pressure, ET opening duration, ET opening frequency, and ET closing pressure were determined before and after intranasal application of xylomethazoline. Results A significantly higher number of ET openings (ET opening frequency) in passive equalization condition could be measured after application of decongestants than before. No significant difference could be found in the values of ET opening pressure, ET opening duration, and ET closing pressure parameters before in comparison with the values after application of xylomethazoline. Conclusion We conclude that xylomethazoline might only have a minor effect during active and passive middle ear pressure equalization. Larger cohorts and targeted application of decongestants should be tested to confirm these preliminary data and to find new evidence on the effects of decongestants.